Panthée : religious transformations in the Graeco-Roman Empire - Bricault, Laurent.; Bonnet, Corinne. (Religions in the Graeco-Roman World, 2013)
Panthée presents a collective reflection relating to the changes that affected the Graeco-Roman Empire and over the long term altered its religious landscapes. Fifty years after the foundation of the series EPRO, the volume aims to avoid the division between the supposedly \'Roman\' or \'Graeco-Roman\' and the \'Oriental\' by linking the available information relating the different major areas, such as the relation between local and global, the place of emotions in relation to soteriological and initiatory aspects, strategies of integration and negotiation of identities. For the first time the leading specialists in every field bring their approaches into contact with one another, and jointly construct a picture of practices and conceptual frames, which, in their diversity and inter-action, model a religious universe whose complexity will help to understand our modern globalising world. Panthée propose une réflexion collective sur les mutations qui ont affecté l'Empire gréco-romain et ont progressivement remodelé ses paysages religieux. Cinquante ans après la création de la collection des EPRO, ce livre ambitionne de dépasser le clivage entre ce qui serait \'romain\', ou \'gréco-romain\', et ce qui serait \'oriental\' en articulant les données disponibles autour de quelques thèmes majeurs, comme les jeux d'échelle entre local et universel, la place du registre des émotions en relation avec les dimensions sotériologiques et mystériques, les stratégies d'intégration et de négociation des identités. Pour la première fois, les meilleurs spécialistes venus de tous les horizons croisent leurs approches et construisent ensemble un tableau des pratiques et des cadres de pensée qui, dans leur diversité et dans leur interaction, dessinent les contours d'un univers religieux dont la complexité aide à penser le monde moderne de la globalisation.